Texting is caring: a content analysis of clinical text messages by hospitalists - Michael Weiner; Claire Elyse Donnelly; Perla L Flores; Areeba Y Kara; Joy L Lee (BMJ Open Quality, 2023)
Background Clinical texting systems (CTS) are widely used in hospitals for team communication about patients. With more institutions adopting such systems, there is a need to understand how texting is being used in clinical practice.Methods We conducted content analysis of 809 randomly selected message threads sent to and from hospitalists in a 9-month window. The process, purpose and content of messages were analysed. We also examined messages for personal content (to identify whether CTS was being used for professional matters) and discussion of near miss errors. The risk levels of these near misses were also assessed.Results Most messages focused on clinical management of patient needs (62%; n=498) and functioned to provide a notification or update regarding clinical care (64%; n=518) or make a request of the recipient (63%; n=510). Personal content was infrequent in message threads (10%; n=80). Five per cent (n=38) of message threads included discussion of a near miss, and most near misses posed low clinical risk overall (66%; n=25).Conclusion Most CTS communication centred around direct clinical management. Fewer messages were focused on non-clinical areas such as administrative tasks or personal communication. Further examination of care delivery, error communication and the consequences of the care discussed in messages would help clinical leaders understand the impact of clinical texting on teamwork and quality of care.